Tác động bất cân xứng của tự do hóa tài chính đối với tăng trưởng kinh tế tại Việt Nam - Lê Thị Thúy, Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper studies the impact of financial liberalization on economic growth in Vietnam, using time series data for the period from Q1/2000 to Q1/2020. The NARDL model is used to examine the disproportionate impact of the expansionary money supply growth variables, lending interest rates and USD/VND exchange rate on Vietnam’s economic growth. The results of this study indicate a general short-run and long-run equilibrium effect between financial liberalization and economic growth. The impact of financial liberalization on economic growth has recorded positive effects and negative effects on economic growth. Policy recommendations for Vietnam include financial liberalization according to the roadmap and focus on proposed financial market management policies.